Effect of catalytic-reactive rejuvenator on structure and properties of aged SBS modified asphalt binders. (20th June 2020) - Wei, Chuanwen; Zhang, Henglong; Duan, Haihui
Highlights: Epoxidized soybean oil and triphenyl phosphine was developed to repair aged SBS structure in asphalt. Physical and rheological properties of rejuvenated SBS modified asphalt were improved. Epoxy group of epoxidized soybean oil can polymerize with hydroxyl of aged SBS chains. Abstract: During aging process of styrene–butadienestyrene copolymer (SBS) modified asphalt (SBSMA), hardening of asphalt matrix combined with degradation of SBS modifier simultaneously occurs. A novel catalytic-reactive rejuvenator containing epoxidized soybean oil (ESO) and triphenyl phosphine (TPP) was applied to repair damaged network structure of SBS. In this study, the effects of different blending time and different content of catalytic-reactive rejuvenator on the pressure aging vessel (PAV) aged SBSMA were investigated. The physical and rheological characteristics of unaged SBSMA, aged SBSMA and rejuvenated SBSMA were investigated, and chemical structure of binders were analyzed by Fourier transform infrared spectroscopy (FTIR) to assess the rejuvenation effect. The results illustrate that based on physical properties and the data reflected by dynamic shear rheometer (DSR) and bending beam rheometer (BBR) parameters, 30 min blending is the optimal preparation condition compared with other blending time (15 min, 1 h and 2 h). With the addition of catalyst and increase of its content, the low-temperature flexibility performance of asphalt is improved according to the ductility and BBR tests, and the softening points and the viscoelastic properties obtained in DSR test are improved first and then decline gradually as a result of the multiple effects of catalyst on repairing SBS structure and softening binder. Based on the results of FTIR test, the increasing of –OH peak and the generating of C–O–C peak indicate that the epoxy group of ESO can be opened by catalyst and then polymerizes with aged SBS chains.